Forecasting the possibility of neonatal early onset sepsis based on perinatal risk factors - Pankaj, Kiran C.; Ganguly, Sristi; Upadhyay, Manas R. (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal sepsis remains a leading cause of neonatal mortality and morbidity, diagnosis of which remains difficult due to variable presentations. With the increasing threat of antimicrobial resistance, it is important to identify perinatal risk factors which are associated with higher incidence of definite sepsis, to initiate empirical antibiotics, while awaiting blood culture reports. Methods: This was hospital based cross-sectional study done in SVPPGIP, Cuttack, Odisha during January 2019 to April 2019, enrolling all neonates ≥37 weeks gestation and aged less than 72 hours, with suspected early onset sepsis. Neonates with TORCH infections, congenital anomalies, syndromic baby or with surgical conditions were excluded. After obtaining informed consent, blood culture was sent for all and their perinatal risk factors noted. Blood culture positive newborns were considered to have definite sepsis. Data was analysed with Chi-square test and percentages, using SPSS 18. Results: Among the 200 cases, incidence of definite sepsis was 26%. The most common risk factor was low birth weight and birth asphyxia. Majority (67%) had single or lesser risk factor and number of risk factors was significantly associated with definite sepsis. A significant association was seen between blood culture positivity with low birth weight (p=0.003), foul smelling liquor (p= 0.025), birth asphyxia (p 0.018) and premature rupture of membranes (p= 0.016). The combination of maternal fever and unclean vaginal examination was also significantly associated with the same. Conclusions: Protocols for initiating empiric antibiotics need to be formulated, taking into account the significant risk factors, in resource limited settings, to avoid resource and time wastage.